Avaliação do risco ecológico e à saúde humana pela contaminação por metais pesados em solos de parques ecológicos urbanos - Fernanda Guerreiro de Paula (2025)
The presence of heavy metals in the soil of urban parks can contaminate adults and children through the oral, dermal, and inhalation routes, causing risks to human health. Therefore, the objective of this study was to quantify the elements As, Pb, Co, Cr, Al Cd, Ni, Co, Fe, Zn, Mn, Mg, Se, P and Mo in the soils of urban ecological parks (EPs) in the city of Campo Grande, MS and estimate the risk of pollution and the risk to human health due to dermal, inhalation and oral contact with heavy metals present in the soil. Analyzes of the physical and chemical characteristics of the soil were carried out, such as organic matter, pH, Al, Bo, S, Cu, Fe, Zn and Mn Ca, Mg, K and P. In addition, microwave digestion using either nitric acid and hydrogen peroxide was used for elemental analysis of soil samples. After microwave digestion, the contents in soil samples were analyzed by inductively coupled plasma optical emission spectrometry (ICP OES). The pH in CaCl2 in the soil of Lago do Amor was 5.8 (classified as a soil type 3), as well as PE Anhanduí was 5.1 (soil type 2), PE Sóter was 4.6 (soil type 1) and PE Águas do Prosa presented higher acidity (3.8) (type 3 soil). In addition, it was verified through the PCA that the values of pH, Mg, Mn, Al, Fe and Zn were the main contaminants, that is, in areas such as PE Anhanduí, a greater influence of the concentration of Al, Fe and Cu prevails, while in Lago do Amor, high concentrations of Mg and Mn and lower pH values predominate. On the other hand, in PE Águas do Prosa there is a greater influence of Zn. With the exception of Al in PE Sóter, the concentration of Al, Fe, Mg, P, Se and Zn in all PEs obtained through ICP OES are higher than those established in Brazil, China and USA. On the other hand, the concentration of As is below the value established in Brazil. According to the Contamination factor (FC), there is moderate contamination by Mo, Ni, Cd and mainly Se in places like PE Lago do Amor, PE Anhanduí, PE Sóter and PE Sóter. The geoaccumulation indices (Igeo) revealed that Lago do Amor is moderately polluted by Cd. The values of Pollution Load Index (PLI) were found to be generally low (0,7  PLI < 1.) in the PE Anhanduí (PLI = 0,7023) and Lago do Amor (PLI = 0,9103), it indicates that there are baseline levels of pollutants. The non-carcinogenic risk index for the evaluated elements was less than one. In addition, oral ingestion was the main route of possible contamination by heavy metals present in the soil of PEs for children, which presented a carcinogenic risk greater than 10-1 for As, Cr and Ni. Therefore, despite the low risk of soil contamination in PEs by heavy metals, special attention should be given to children exposed to these soils in the long term due to the likelihood of developing cancer